Refugee healthcare needs and barriers to accessing healthcare services in New Zealand: a qualitative phenomenological approach - Bafreen Sherif; Ahmed Awaisu; Nadir Kheir (BMC, 2022)
Abstract Background Refuges and asylum seekers have specific healthcare needs; however there has been insufficient attention and effort to address these needs globally. Furthermore, effective communication between healthcare providers and refugees remains poor, further widening the imbalanced power dynamics. The aim of this research project was to examine refugee healthcare needs and current barriers to accessing healthcare services in New Zealand, and to propose solutions by exploring the perceptions, attitudes, beliefs, and opinions of key stakeholders regarding refugee healthcare needs within the scaffold of health and social care systems. Methods We conducted semi-structured interviews between September and December 2018 with 18 purposively selected refugee service provider stakeholders in New Zealand using an interview guide that addressed healthcare needs, existing barriers to access healthcare services, and perceived future healthcare delivery solutions. Results Thematic analysis of emergent themes of this study indicated the need for a national framework of inclusion, mandating cultural safety training of frontline personnel, improving access to interpreters and cultural mediators, and establishing the role of patient navigators. Barriers to accessing health services included entrenched social health determinants such as housing scarcity and disenfranchised community environments; refugee health-seeking behaviour and poor health literacy; along with existing social support networks. We propose that healthcare delivery should focus on capacity building of existing services, including co-design processes with refugees and asylum seekers and increasing funding for refugee-specific health service via the implementation of an overarching national strategy. Conclusion Based on the findings of this study, refugee organisations and their frontline personnel should seek to address the deficiencies identified in order to provide equitable, timely and culturally-accessible healthcare services for refugees in New Zealand and in comparable countries.